Kajian bisnis perikanan tangkap gurita (Octopus sp.) dengan alat tangkap Ganco di Desa Waiiti Barat Kecamatan Tomia Kabupaten Wakatobi - Vasadhine, Hursan; La Ola, La Onu; Mansyur, Akhmad; Abdullah; Risfandi; Siang, Roslindah Daeng (Universitas Halu Oleo, 2023)
This study aims to (1) examine the cost of good sold received by octopus fisherman (2) assess the profit margins of octopus fisheram using hook fishing gear every time fishing trip. This research was conducted in the West Waitii Village, Tomia District Wakatobi Regency in March-April 2020. The method used in this study was census method with a number of respondents 32 people. Primary data was collected by direct interviews using a questionnaire, including fuel costs, conmsumption, number of catches pertrip, and selling prices, while secondary data consisted of population, education level nuber of dependents of fisherman’s families, and other data related to this research. The data analyzed using the formula Fixed Costs and Variable Costs, Total Costs. The standard deviation is used to identify and provide an overview of the distribution of the data to the average data, and to categorize costs. The results of the analysis show that: (1) The cost of goods soldfor octopus fisheran average is Rp8.887.(2) The average profit of fisherman cacthing octopus with hook fishiing gear is Rp160.599/Trip. Keywords : Octopus Fisherman, Cost of Good Sold, Profit, Tomia